Evaluation of the attractiveness of different gingival zeniths in smile esthetics - Suzy Nomura; Karina Maria Salvatore Freitas; Paula Patrícia Cotrin da Silva; Fabricio Pinelli Valarelli; Rodrigo Hermont Cançado; Marcos Roberto de Freitas; Renata Cristina Gobbi de Oliveira; Ricardo Cesar Gobbi de Oliveira
ABSTRACT Objective: To evaluate the smile attractiveness of different gingival zeniths by general dentists, orthodontists and laypersons and the esthetic perception in the symmetric and asymmetric changes in gingival zeniths. Methods: Posed photographs of five patients were taken and digitally manipulated in Keynote software, in the gingival zenith region, in increments of 0.5 to 1mm in maxillary central and lateral incisors, symmetrically and asymmetrically, in nine different ways for each patient. The photos were then uploaded to a website, where evaluators (general dentists, orthodontists and laypersons) could observe and vote according to their esthetic perception, scoring from 1 to 10, 1 being the least attractive and 10 the more attractive. Kruskal-Wallis and Mann-Whitney tests were used for comparison. Results: Asymmetric gingival zeniths were less attractive than symmetrical gingival zeniths; gingival zenith differences greater than 1mm were perceptible in the smile attractiveness, both by laypersons, general dentists and orthodontists. When comparing maxillary central incisors with maxillary lateral incisors, the aesthetic change performed in the central incisors are more perceptible than those performed in lateral incisors, both symmetrical and asymmetrical. In a general way, orthodontists and general dentists are more critical in the evaluation and perception of gingival zenith changes, with the laypersons perceiving this change only from 1mm of maxillary right central incisor asymmetrical change. Conclusions: Asymmetric gingival zeniths are less attractive than symmetrical ones. Gingival zenith differences greater than 1mm are perceptible in the smile attractiveness. Orthodontists and general dentists are more critical in evaluating smile esthetics.